The Importance of Impoundment interception in Simulating Riverine Dissolved Organic Carbon - JiaoJiao Liu; JunZhi Liu; XinZhong Du; RenKui Guo; Zheng Duan; BinJie Yuan; YongQin Liu (Water Resources Research)
Abstract Modeling of riverine dissolved organic carbon (DOC) dynamics is of great importance for the global carbon budget. Impoundment interception changes the travel time of water and DOC from upslope contributing areas, exerting substantial influence on riverine DOC dynamics in the catchments with many impoundments. However, the impact of impoundment interception representation on riverine DOC modeling has not been evaluated so far. This study investigated to what extent impoundment interception representation affects DOC simulations using a newly developed catchment‐scale DOC model, which can represent the upslope contributing areas of impoundments and the impoundment interception process. The results showed that streamflow and DOC load simulation were well simulated regardless of whether impoundment interception was represented, but the simulation of DOC concentrations was satisfiable only when impoundment interception was taken into account. The simulation without impoundment interception produced unrealistic fluctuation of DOC concentration due to the direct mixing of DOC from different sources with contrasting concentration gradients. These results underscored the significance of employing an appropriate model structure for riverine DOC simulation. It is strongly recommended that DOC concentration be utilized for model evaluation in order to attain robust simulation outcomes. Moreover, the newly developed model in this study keeps a balance between the completeness of process presentation and model complexity, occupying a unique “ecological niche” among catchment‐scale riverine DOC models.